AB1113-HPR Description of The Spare Time Utilization and Relationship between Functionality and Disease Activity in A Colombian Rheumatoid Arthritis Cohort. (15th July 2016) - Rangel, E.; Villarreal, L.; Santos-Moreno, P.; Palacio, N.; Castro, C.; Buitrago-Garcia, D.
Abstract : Background: Spare time utilization is defined as delectable and non-remunerated activities that a person realizes through its vital cycle. In rheumatoid arthritis (RA) patients this activities might be altered by multiple causes as functional deterioration, psychological problems and social exclusion. Objectives: The aim of this study is to describe the spare time activities and possible relationship with disease activity and functionality of a RA patient's cohort. Methods: A descriptive cross sectional study was realized. A revision of medical records of a cohort of RA patients was performed, including occupational therapy records. For all patients DAS28, HAQ, clinical evaluation and interests check list were made. Percentages, averages and Pearson's statistics were used for clinical and occupational variables. Results: Total sample of patients was 1298, 1048 (80%) were women and 250 (19%) were men. Patients had a DAS28 2.6 in average ± 1.1; mean age was 55.1 ± 8.8 years; 846 (65%) were in remission, 205 (16%) were in low disease activity, 208 (16%) in moderate disease activity and 42 in severe disease activity (3%). Regarding education, 6% were illiterate, 44% had elementary school, 33% high school, 8% had a technical degree and only 7% had college level. In the spare time activities the most frequent were: mixed activities 26% housekeeping 24%, and intellectual activities 15% and handcrafting activities 12%. It was not established correlation between spare time use and disease activity or functionality. Conclusions: Even we did not find a statically correlation between practicing spare activities or not practice and the disease activity, we found that practicing sports improves in men DAS score. Most patients in this cohort prefer mixed activities as their main spare time activity, and other main frequent activities were handcrafting or home activities; perhaps it's important to maintain in this cohort low activity disease and make more studies about this topic because study suggests that male who did only academic activities had more active disease. Disclosure of Interest: None declared